2021
DOI: 10.1523/eneuro.0157-21.2021
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering Spinal Endogenous Dopaminergic Mechanisms That Modulate Micturition Reflexes in Rats with Spinal Cord Injury

Abstract: Spinal neuronal mechanisms regulate recovered involuntary micturition after spinal cord injury (SCI). It is recently discovered that dopamine (DA) is synthesized in the rat injured spinal cord and is involved in lower urinary tract (LUT) activity. To fully understand the role of spinal DA-ergic machinery in micturition, we examined urodynamic responses in female rats during pharmacological modulation of the DA pathway. Three to four weeks after complete thoracic SCI, L-DOPA administered intravenously during bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 83 publications
0
11
0
Order By: Relevance
“…3 A , arrowheads). This region has previously been identified as the location of inhibitory and excitatory interneurons involved in micturition ( Vizzard et al, 1995 ; Araki and de Groat, 1996 ; de Groat et al, 2015 ), some of which express TH ( Hou et al, 2016a , 2021 ; Wiedmann et al, 2021 ). Confocal microscopy confirmed close associations between LUT afferents and TH neurons in this region, however the majority of LUT afferents were not near TH neurons ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 A , arrowheads). This region has previously been identified as the location of inhibitory and excitatory interneurons involved in micturition ( Vizzard et al, 1995 ; Araki and de Groat, 1996 ; de Groat et al, 2015 ), some of which express TH ( Hou et al, 2016a , 2021 ; Wiedmann et al, 2021 ). Confocal microscopy confirmed close associations between LUT afferents and TH neurons in this region, however the majority of LUT afferents were not near TH neurons ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…One possibility is that local circuit interneurons regulating LUT function extend more rostrally than LUT-regulating preganglionic neurons. Although no chemoarchitectural markers have been identified to delineate this entire group of interneurons, a subpopulation near the SPN expresses TH ( Hou et al, 2016a , 2021 ). In the current study, we found that TH neurons extend more rostrally than preganglionic neurons and we have previously reported that cystometry evokes c-Fos expression in this region and throughout the length of L6 ( Wiedmann et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…D 2 -like receptors include D 2 , D 3 , and D 4 and they inhibit adenylyl cyclase through G i/o proteins and thus suppress neural activity. Throughout the spinal cord [17] Pronociception [17] Micturition [398,399], cardiovascular function [400],…”
Section: Dopaminergic Fiber Pathwaysmentioning
confidence: 99%
“…Superficial laminae and lamina X [17] Antinociception, pronociception [17] Micturition [398,399] SCH 23390 [398][399][400]402,403], SCH 39166 [401,404] Aripiprazole [405], apomorphine [300,398,400,406], SKF 83959…”
Section: Dopaminergic Fiber Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation